PENGARUH MODEL PEMBELAJARAN SELF-DIRECTED LEARNING BERBASIS PLATFORM EDUCAPLAY TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA KELAS IV DI MIN 2 BANDAR LAMPUNG - Tantri Aprillita; Chairul Anwar; hasan sastra negara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is motivated by the low level of students’ mathematical problem-solving abilities. One contributing factor is the use of learning models that do not adequately support the development of students’ learning independence. Therefore, a learning approach is needed that can enhance active engagement and provide opportunities for students to independently direct their learning processes. The Self-Directed Learning model integrated with the Educaplay platform was selected as an alternative, as it is considered capable of creating a varied, interactive, and student-centered learning experience. This study aims to examine the effect of the Educaplay-based Self-Directed Learning model on the mathematical problem-solving abilities of fourth-grade students. The research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The sampling technique used was purposive sampling. The research instrument was an essay test designed to measure mathematical problem-solving ability. The population consisted of all fourth-grade students, while the sample comprised 56 students, including 28 students in the experimental group and 28 students in the control group. Data analysis included the Shapiro–Wilk normality test, Levene’s test for homogeneity of variance, and hypothesis testing using the independent samples t-test. The results indicated that the significance value (2-tailed) was 0.000, which is less than 0.05. Therefore, H₀ was rejected and Hₐ was accepted, leading to the conclusion that the Educaplay-based Self-Directed Learning model has a significant effect on the mathematical problem-solving abilities of fourth-grade students at MIN 2 Bandar Lampung.